Urinary excretion of 5-L-oxoproline (pyroglutamic acid) during early life in term and preterm infants. Issue 3 (1st May 1997) - Jackson, Alan A; Persaud, C; Hall, M; Smith, S; Evans, N; Rutter, N
Abstract : Urinary 5-L-oxoproline was measured in term and preterm infants from shortly after birth until 6 weeks of postnatal age to determine their ability to synthesise glycine. In term infants the excretion was five to 10 times that seen in normal adults, increasing from 105 μmol/mmol creatinine in the first 72 hours after birth to 170 μmol/mmol creatinine at 6 weeks of age. There was a significant inverse linear correlation between the excretion of 5-L-oxoproline and length of gestation or birthweight. By 6 weeks of age there was no longer a significant difference in 5-L-oxoproline between term and preterm infants. There was no difference in the excretion of 5-L-oxoproline between boys and girls, or between infants fed on human milk or an artificial formula. If, in part, variability in the excretion of 5-L-oxoproline is determined by the extent to which the endogenous formation of glycine is adequate, then glycine formation may be marginal during early life, more so in preterm than in term infants, providing additional evidence that glycine is a conditionally essential amino acid in the neonate.